“Music Evoked Pictures in Her Mind”: Sensory and Artistic Synaesthesia in Kate Chopin’s "The Awakening" - Piñero Gil, Eulalia (Complutense Journal of English Studies, 2015)
Music dominates Kate Chopin’s literature but in her most acclaimed novel, The Awakening, it becomes a powerful leitmotif that evokes transformation, awareness and initiation. In various ways, Chopin emphasizes the emotional power of music and Edna Pontellier’s awakening is accompanied by music throughout the novel. Nevertheless, critics have surprisingly ignored the decisive role music has in the novel as a sensorial structure and synaesthetic channel in Edna’s rebirth as a new woman in the sense that music is the natural way through which the protagonist channels her emotions and her artistic creativity. This essay explores how Kate Chopin creates in The Awakening an enduring artistic and sensorial synaesthesia, through the extensive use of music, in which one type of sensation triggers another sensorial response in a different perceptual domain. In this way, music, which is the most relevant artistic leitmotif and sensation in the novel, evokes and blends not only images in Edna’s mind, but all types of physical and emotional feelings that contribute in a decisive way to the protagonist’s transcendental metamorphosis.